2012
DOI: 10.2174/157489212798357958
|View full text |Cite
|
Sign up to set email alerts
|

Recent Patents on Anti-Telomerase Cancer Therapy

Abstract: Telomerase, a specialised RNA-directed DNA polymerase extends and stabilises the telomeres at the ends of the eukaryotic chromosomes. The progressive loss of telomeres results in limited number of cell divisions and has been linked to the mechanism of human cellular ageing. Tumour cells marked by indefinite proliferation have stable telomere length maintained by telomerase. The differential expression of the telomerase enzyme in normal and cancer cells have led to the evolution of tumour specific anti-telomera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 75 publications
0
35
0
Order By: Relevance
“…Several therapeutic strategies for overcoming activated telomerase have been explored, 2 including targeting the telomerase holoenzyme or the human telomerase reverse transcriptase (hTERT) subunit, targeting telomeric Gquadruplexes, inhibiting telomerase RNA, and using immune therapy directed at hTERT as a tumor antigen. Imetelstat, an antisense 13-mer oligonucleotide targeted to hTERT, has shown preclinical promise with anticancer activity in breast, brain, pancreas, and liver cancer models.…”
Section: Introductionmentioning
confidence: 99%
“…Several therapeutic strategies for overcoming activated telomerase have been explored, 2 including targeting the telomerase holoenzyme or the human telomerase reverse transcriptase (hTERT) subunit, targeting telomeric Gquadruplexes, inhibiting telomerase RNA, and using immune therapy directed at hTERT as a tumor antigen. Imetelstat, an antisense 13-mer oligonucleotide targeted to hTERT, has shown preclinical promise with anticancer activity in breast, brain, pancreas, and liver cancer models.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly increased telomerase expression and activity has been observed in nearly 90 % of cancer cells, suggesting its potential as an anticancer drug target [19,20]. Currently, therapeutic approaches to inhibit telomerase activity have focused on small molecular inhibitors, gene therapy, and immune therapy [21][22][23][24][25]. Several antitumor drugs targeting telomeres and telomerase such as GRN163L have been developed and are currently in clinical trials (phase I/II) [26][27][28][29][30][31][32][33]; however, suppression of tumor growth by telomerase inhibition did not occur immediately.…”
Section: Introductionmentioning
confidence: 99%
“…Studying anti-telomerase potential of various deoxyguanosine nucleotide analogs, Tendian et al [40] observed that 2', 3'-dideoxyguanosine 5'-triphosphate, 6-thio-2'-deoxyguanosine 5'-triphosphate (T-dGTP), carbovir 5' triphosphate (CBV-TP), and D-carbocyclic-2'-deoxyguanosine 5'-triphosphate (D-CdG-TP) were able to inhibit telomerase activity by 50% with half maximal inhibitory concentrations (IC50) of 3±2µM, 8±2µM, 6±1.5µM and 11±2µM, respectively. In addition, compounds such as 7-deaza-2'-deoxyguanosine-5'-triphosphate (7-deaza-dGTP) and 7-deaza-2'-deoxyadenosine-5'-triphosphate (7-deazadATP) potentially inhibited telomerase activity by competing with natural substrates dGTP and dATP, respectively and hence getting incorporated into telomeric DNA by telomerase [40].…”
Section: Telomerase Inhibitorsmentioning
confidence: 99%
“…In addition, compounds such as 7-deaza-2'-deoxyguanosine-5'-triphosphate (7-deaza-dGTP) and 7-deaza-2'-deoxyadenosine-5'-triphosphate (7-deazadATP) potentially inhibited telomerase activity by competing with natural substrates dGTP and dATP, respectively and hence getting incorporated into telomeric DNA by telomerase [40]. However, they act as poor substrates for telomerase and lead to the dissociation and decreased processivity of telomerase.…”
Section: Telomerase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation